3D food printing: nutrition opportunities and challenges. Issue 2 (24th September 2020) - Burke-Shyne, Suailce; Gallegos, Danielle; Williams, Tim
Abstract : Purpose: To explore the nutrition opportunities and challenges for 3D food printing. Design/methodology/approach: Using a qualitative design, semi-structured interviews were conducted with experts from the field of nutrition or with a technical understanding of 3D food printing and a thematic analysis undertaken. Findings: Four themes emerged: potential uses, sustainability, technical issues and ethical and social issues. The primary use identified was for texture-modified diets. Other uses include personalised nutrition and for novelty purposes. Interviewees indicated food printing may aid sustainability by reducing food waste, using food by-products and incorporating eco-friendly foods. The main technical issues were speed, cost and inability of the technology to move between textures. The latter is a limiting issue if the technology is purported to be used for texture-modified diets. Ethical and social issues raised included the acceptability and high degree of processing involved in printed foods. Originality/value: This research highlights the need for nutrition issues to be considered as 3D food printing technology develops.